Digital Earth Surface Model for The Estimation of Solar Panel Electric Power Towards Renewable Energy - Baskara Suprojo; Westi Utami; Luthfi Adela Saraswati; Diffa Alifia Nabila; M Nazir Salim (Department of Urban and Regional Planning, Diponegoro University, 2022)
The development of Geographic Information Systems (GIS) is able to create future value in various sectors and become a solution to the problem of limitations and disparity of electricity resources in Indonesia. This condition encourages GIS to be an analytical solution to the problem of electricity resources, which is by utilizing solar radiation as a source of renewable energy. This study aimed to optimize GIS in the use of solar radiation on the slope of building roofs which affects the estimated number and average electric power. This study used the mixed method. Research data includes aerial photos, which were analyzed digitally using the area of solar radiation and the slope angle of building roofs so as to produce a spatial analysis of the utilization of solar panels on Derawan Island. The data analysis showed that buildings in Derawan Island can produce 17,355.254 mWh per year with each building producing an average of 28,686 kWh annually. The result of the study is expected to encourage the realization of the use of renewable energy as part of the SDGs by utilizing solar panels as a source of electricity, replacing fossil-derived energy. This study is also expected to be applied in other small inhabited islands to support the sustainability of electricity use and increase the use of renewable energy.